Patriotic values of young men of military age involved in sports in the aspect of sociological analysis - Serykh A.B. ,; Buksha L.F. ,; Osipova Е.V. ,; Nazarskaya E.N. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the features of the development of patriotic values, the formation of civic consciousness and attitudes towards military service and defense of the Fatherland among young men of military age involved in sports. Methods and structure of the study. Step-by-step empirical work was carried out on the basis of the Kaliningrad military commissariat with young men of military age (310 people 17-18 years old), students of educational institutions in Kaliningrad. Diagnosis was carried out using questionnaires of constructive patriotism (S.V. Vasilyeva, A.V. Miklyaeva), attitudes towards military service and defense of the Fatherland, and methods for assessing the level of formation of civic consciousness. Results and conclusions. The diagnostic results obtained made it possible to identify the features of the development of patriotic values, the formation of civic consciousness and attitudes towards military service and defense of the Fatherland among young men of conscription age who are and are not involved in various sports. Sports have a positive impact on the development of patriotic values, the formation of civic consciousness and attitudes towards military service and defense of the Fatherland among young men of military age.